2007
DOI: 10.1097/mpg.0b013e31812e012f
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Acid‐suppressive Effects of Esomeprazole in Infants 1–24 Months Old With Symptoms of Gastroesophageal Reflux Disease

Abstract: Oral treatment with esomeprazole 0.25 mg/kg and 1 mg/kg was well tolerated and provided dose-related acid suppression, dose-related exposure to esomeprazole, and decreased esophageal acid exposure in infants 1-24 months old with GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…In general, the exposure increased more than proportionately with an increase in dose, from 10 mg to 20 mg. The inter‐individual variability, as well as the age, weight and dose dependency are all consistent with previous findings in Japanese adults, and in Caucasian children . The more pronounced variability in children may be partly explained by the lower number of plasma samples in children, potential loss of substance/dose due to spitting/vomiting in some smaller children, and, further, the age‐dependent maturation of the CYP liver enzymes …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the exposure increased more than proportionately with an increase in dose, from 10 mg to 20 mg. The inter‐individual variability, as well as the age, weight and dose dependency are all consistent with previous findings in Japanese adults, and in Caucasian children . The more pronounced variability in children may be partly explained by the lower number of plasma samples in children, potential loss of substance/dose due to spitting/vomiting in some smaller children, and, further, the age‐dependent maturation of the CYP liver enzymes …”
Section: Discussionsupporting
confidence: 88%
“…Although the number of patients who consented to intragastric pH monitoring was small, a longer duration of gastric pH >4 with esomeprazole treatment was indicated, as has been seen in previous studies in Japanese adults (Dr Per Lundbord, unpubl. data, 2004) and Caucasian children …”
Section: Discussionmentioning
confidence: 99%
“…Notable works that may translate to neonatal population include: 1) development of automated impedance manometry for pressure flow analysis 63,6870 , 2) effect of GERD therapies in infants and children 7177 , and the 3) effect of stimulus characteristics on esophageal function 78,79 .…”
Section: ) Pathophysiology Of Aerodigestive Systemsmentioning
confidence: 99%
“…On the contrary, a recent study by Omari et al [92], on the effectiveness of esomeprazole in preterm infants, demonstrated a significant decrease in the number of GERD-related symptoms, a remarkable reduction of the overall esophageal acid exposure and, as previously found [93], a lowered number of acid bolus reflux episodes whereas, as expected, nonacid GER features were not influenced. However, these results were not controlled for placebo effects; therefore, they should be confirmed in further placebo-controlled trials.…”
Section: Pharmacological Therapymentioning
confidence: 46%